2021
DOI: 10.22434/ifamr2020.0094
|View full text |Cite
|
Sign up to set email alerts
|

Rural extension and technical efficiency in the Brazilian agricultural sector

Abstract: In this paper, we identify the effect of rural extension on the productive performance of Brazilian agricultural establishments, using technical efficiency as a measure of farm performance. The data used is drawn from the microdata of the 2006 Agricultural Census, accessed directly from the IBGE secrecy room. For this, we use an approach that combines the stochastic production frontier, considering selection bias in the adoption of rural extension (Heckman’s approach) and entropy balancing. We find that rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(28 reference statements)
1
9
0
6
Order By: Relevance
“…Our simulations indicate that recovery of degraded pasture can increase the stocking rate, while forest restoration enhances conservation and supports FC compliance. However, several drivers act as We find that efficiency is positively related to RAS ( p < 0.01): the larger the area of livestock assisted by RAS, the greater the efficiency, in line with other recent studies [52][53][54][55]. Brazil once had one of the largest and most efficient public RAS programmes in the world, but they have been in decline since the fiscal crisis in the 1990s.…”
Section: Financing the Recovery Of Degraded Pasturessupporting
confidence: 87%
See 3 more Smart Citations
“…Our simulations indicate that recovery of degraded pasture can increase the stocking rate, while forest restoration enhances conservation and supports FC compliance. However, several drivers act as We find that efficiency is positively related to RAS ( p < 0.01): the larger the area of livestock assisted by RAS, the greater the efficiency, in line with other recent studies [52][53][54][55]. Brazil once had one of the largest and most efficient public RAS programmes in the world, but they have been in decline since the fiscal crisis in the 1990s.…”
Section: Financing the Recovery Of Degraded Pasturessupporting
confidence: 87%
“…Although they still provide essential services, especially to the poorest producers, they have very limited budgets and human resources, and have even been discontinued in some regions. Private RAS have been consolidating in the country among farmers, usually services involving chemical input and machinery purchases, but they are still little noted among ranchers [ 54 ]. In fact, according to the latest Agricultural Census, only 1 out of 10 cattle ranchers declared to have been assisted or to have contracted RAS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The provision of governmental rural extension mostly targets family-owned farms but also reaches non-family-owned farms. Freitas et al [48] found that extension was provided to all farm sizes in all regions of Brazil. Table 3 shows that MSCM is positively associated with governmental rural extension and access to credit.…”
Section: Econometric Resultsmentioning
confidence: 99%